Identification of gut bacteria reductases that biotransform steroid hormones - Gabriela Arp; Angela K. Jiang; Keith Dufault-Thompson; Sophia Levy; Aoshu Zhong; Jyotsna Talreja Wassan; Maggie R. Grant; Yue Li; Brantley Hall; Xiaofang Jiang (Nature Communications)
Abstract The metabolism of steroid hormones by the gut microbiome is increasingly recognized as a key factor in human health; however, the specific enzymes mediating these transformations remain largely unidentified. In this study, we identify Δ4-3-ketosteroid 5β-reductase, 3β-hydroxysteroid dehydrogenase/Δ5-4 isomerase, and Δ6-3-ketosteroid reductase enzyme families encoded by common human gut bacteria. Through phylogenetic reconstruction and mutagenesis, we show that 5β-reductase evolved to specialize in converting both natural and synthetic 3-ketosteroid hormones into their 5β-reduced derivatives, while Δ6-3-ketosteroid reductase adapted to produce Δ6-reduced derivatives. We also find that the novel 3β-hydroxysteroid dehydrogenase/Δ5-4 isomerase is fused with 5β-reductase in multiple species, streamlining the conversion of pregnenolone, a 3β-hydroxy-5-ene and steroid hormone precursor, into epipregnanolone. Through metagenomic analysis, we reveal that these enzymes are prevalent in healthy populations and enriched in females compared to males. These findings lay the groundwork for mechanistic investigations into how microbial steroid metabolism modulates host hormonal physiology.